On-line Condition Monitoring in Industrial Lubrication and Tribology - Myshkin, Nikolai K. (Applied Condition Monitoring,, 2018)
This book offers readers a concise yet comprehensive introduction to a set of diagnostic methods for on-line condition monitoring of lubricated tribosystems used in industry. It covers the latest trends in on-line tribodiagnostics, an important and rapidly developing area of tribology. The book also reports on new tools as they have been developed and applied by the authors. A special emphasis is given to the physical fundamentals of opto-magnetic detectors, ferro-analyzers and analyzers of metal particles in lubricated tribosystems, as well as fluorescence methods for real-time oil monitoring in compressors, hydraulic systems and electrical transformers. Further, the book discusses other important issues such as the monitoring of water content in oil, and presents techniques for measuring soot content in oil in diesel engine oils. Lastly, it describes the modular intelligent (SMART) diagnostic system for vehicles. Mainly intended for researchers, industrial and automotive engineers developing cost-effective techniques and sensors for the on-line monitoring of lubricating oil, the book also offers a valuable source of information for students and project managers in the manufacturing, energy, oil and gas, and automotive industry.